Methods for analysing morphodynamics of tidal inlets - Willemsen, Pim; Hulscher, Suzanne; Vermaas, Tommer (Student Undergraduate Research E-journal!, 2015)
A major part of the world’s coast is formed by sequences of barrier islands and tidal inlets. Tidal inlets are highly dynamical systems, influencing the surrounding environment as well. The inlets contain morphological units: tidal channels, sandbanks, etc. A method is developed regarding the analysis of morphological units in space and time, including quantitative volumetric analysis. The method is applied to the Ameland inlet, a study site situated in the Dutch Wadden Sea. The dynamics of tidal inlets: e.g. deformation, displacement, whether a channel is filling up, etc. can be analysed using the developed method.